Wrongful Discrimination Without Equal, Basic Moral Status - Lippert-Rasmussen, Kasper (Ethical theory and moral practice, 2023)
Many theorists think that discrimination is wrongful because it involves treating discriminatees as if they have a lower moral status than others when in fact all people are moral equals. However, there are strong reasons, expounded by Peter Singer and others, to doubt that all people are indeed moral equals. While it may turn out that, ultimately, these reasons can be shown to be unsound, we cannot rule out the possibility that we are not all moral equals. If we are not, discrimination cannot be wrong because it involves failure to treat people as moral equals. With this in mind, I propose two anti-inegalitarian accounts of the wrongness of discrimination - "anti-inegalitarian" rather than "egalitarian" because, strictly speaking, they do not posit equality of status, and "anti-inegalitarian" rather than "inegalitarian" because they reject almost all (and in the case of one of them, all) inequalities in status. These two accounts have many of the attractions of the moral equality account. Being immune to Singerian doubts about moral equality is also a strength of the accounts because it means that they are not hostage to the outcome of the intricate debate over moral equality. Lastly, the anti-inegalitarian accounts I propose are in some ways preferable to the moral equality account because they have certain implications for the wrongness of discrimination that an account given in terms of moral equality does not have, and which egalitarians so far have not theorized.